Development of a Korean Safety Ladder With Ensured Overturning Stability - Giyeol Lee; Jeongjae Park; Ilnam Lee; Jongmoon Hwang (Safety and Health at Work)
Background: We have developed the Korean safety ladder as part of development of new safety technologies that can be accepted in industrial sites and would like to introduce the testing process to secure safety. Methods: The test load and horizontal force prescribed by ANSI A14.7 and EN131-7 standards for only the overturning stability test were applied to calculate the weight required for securing overturning stability according to standards and installation of outrigger with the variables of the height of platform, the angle of inclination of the worker, and the size of the platform. Results: The weight of a Korean safety ladder required for securing overturning stability according to the height is as follows: as mentioned by the ANSI A14.7, it is stable regardless of the weight when an outrigger. By the EN131-7 standard, a 5-step ladder is stable regardless of the weight, but 54 kg or more of weight is required for an 8-step ladder when an outrigger is installed. When there is no outrigger, 122 kg and 251 kg are required for 5-step and 8-step ladders, respectively. Conclusion: It is necessary to restrict inclined working on the platform at less than 66° of inclination angle by the EN131-7 standards and secure 43 kg or more of weight in the minimum width of a platform of 400 mm or expand the ladder width or open length of the outrigger.